A novel antimüllerian gene mutation in a woman with high antral follicle count and extremely low serum antimüllerian hormone levels - Laura Melado, M.D., Ph.D; Barbara Lawrenz, M.D., Ph.D; Jonalyn Edades, B.S; Ajay Kumar, Ph.D; Human Fatemi, M.D., Ph.D (Elsevier, 2024)
Objective: To report a case with a distinct difference between the ovarian reserve parameters of antimüllerian hormone (AMH) levels, antral follicle count (AFC), and follicle-stimulating hormone levels caused by a novel homozygous missense variant in the exon 1 of the AMH gene [NM_000479.4:c259G>A, p.(Val87Met)]. Design: Case report. Setting: Tertiary referral in vitro fertilization clinic. Patients: A 33-year-old woman, G4P4A0E0L4, with a BMI of 25.33 kg/m2, high AFC, and repeated extremely low systemic AMH levels, was detected and measured using multiple enzyme-linked immunosorbent assays. Interventions: Antimüllerian hormone analysis with multiple assays, whole exome sequencing through next generation sequencing to diagnose the missense variant, and inhibin B measurement. Main Outcomes Measures: Genetic counseling and two subsequent ovarian stimulations for successful fertility preservation. Results: Detection of the [NM_000479.4:c259G>A, p.(Val87Met)] variant in the AMH gene. Retrieval and cryopreservation of four euploid blastocysts and 26 metaphase II oocytes. Conclusions: AMH gene mutations can lead to the absence of systemic AMH levels and might be discordant to other ovarian reserve markers like AFC, follicle-stimulating hormone, and inhibin B, without affecting the ovarian response to ovarian stimulation. Clinicians should not rely exclusively on AMH levels for ovarian stimulation. When severely reduced AMH levels are found in patients with high AFC, AMH variants should be suspected, and fertility treatments should be tailored adequately.